2015
DOI: 10.1371/journal.pone.0121840
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma and Personal Mastery: Their Influence on Emotional Reactivity to Everyday Events in a Community Sample of Middle-Aged Adults

Abstract: Childhood trauma is associated with premature declines in health in midlife and old age. Pathways that have been implicated, but less studied include social-emotional regulation, biological programming, and habitual patterns of thought and action. In this study we focused on childhood trauma’s influence via alterations in social-emotional regulation to everyday life events, a pathway that has been linked to subsequent health effects. Data from a 30-day daily diary of community residents who participated in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 71 publications
(80 reference statements)
5
51
2
4
Order By: Relevance
“…Our results broadly replicated findings from Glaser et al (2006), Infurna et al (2015) and Lardinois et al (2011), showing higher global NA in response to daily stress for those reporting more CT, specifically sexual abuse. Although these studies did not examine differences in trauma type, our results suggest that early sexual abuse rather than early physical abuse may have driven this observed effect.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results broadly replicated findings from Glaser et al (2006), Infurna et al (2015) and Lardinois et al (2011), showing higher global NA in response to daily stress for those reporting more CT, specifically sexual abuse. Although these studies did not examine differences in trauma type, our results suggest that early sexual abuse rather than early physical abuse may have driven this observed effect.…”
Section: Discussionsupporting
confidence: 85%
“…For example, Glaser, van Os, Portegijs and Myin-Germeys's (2006) study of adults with histories of somatic complaints, Lardinois, Lataster, Mengelers, van Os and Myin-Germeys's (2011) study of adult patients with recent onset non-affective psychotic disorder and Infurna, Rivers, Reich, and Zautra's (2015) study of middle-aged adult community residents all found that individuals with a history of CT, compared to individuals without CT histories, showed stronger daily stress-reactivity. Although the results of these studies support the notion that CT increases vulnerability to later-life ED, several aspects of measurement require further investigation.…”
Section: Stress-reactivity and The Daily Process Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…101 Hypervigilance and other fear-related motivational states have been associated with high levels on the anxiety dimension [G] of insecure attachment. Differential responsiveness to social reward and high reactivity to social stressors have been identified among individuals with a history of abuse, 103 and a reduction in ventral striatum activation following social rewards has been found in those with insecure attachment characterized by avoidance. 104 A history of child abuse and attachment insecurity, as well as contemporaneous social factors, could set the stage for future disability and impair both physiological and psychological processes associated with resilient adaptation to chronic pain.…”
Section: Social Factorsmentioning
confidence: 99%
“…Some authors used biological programming in a manner synonymous with biological embedding, demonstrating a clear overlap of these concepts (Rutter & O’Connor 2004, McArthur et al . 2005, Rutter 2006, Schuler & Auger 2010, Infurna et al . 2015, Pariante 2015).…”
Section: Resultsmentioning
confidence: 99%